UNIVERSITY AS AN INSTITUTE FOR REGIONAL DEVELOPMENT - Evgeniya I. Mikhailova; Vasilii M. Savvinov (Высшее образование в России)
The example of the North-Eastern Federal University shows that the solution of the problems of innovative regional development taking into consideration the needs and interests of the key stakeholders requires significant institutional change and transformation of the role of universities in the development of the region. Universities start to take on new roles as generating centers of new knowledge, ideas, and initiatives, as centers for accumulation scientific and technological potential of the regions, as urban studies institutes, «think tanks », and the centers of attraction of high-tech industries to the region. In this framework, nature of university development management changes and aims primarily at the deployment of new practices that enhance the competitive positions of the university. This article reveals some trends transforming the role of universities in regional development on the NEFU example.